Editorial 24:2 - Braude, Stephen (Journal of Scientific Exploration, 2010)
The Journal of Scientific Exploration is devoted to the open-minded examination of scientific anomalies and other topics on the scientific frontier. Its articles and reviews, written by authorities in their respective fields, cover both data and theory in areas of science that are too often ignored or treated superficially by other scientific publications. This issue of the Journal is devoted to a single multifaceted topic: mediumship, and mental mediumship in particular. The authors of the lead paper describe several varieties of mediumship, and propose that the psychosocial and cultural aspects of mediumship are as important as its psychophysiological features. They consider the differences between spiritism and spiritualism, the relevance of the trance state to mediumship, and the extent to which processes properly considered mediumistic infiltrate many everyday human activities. The next paper surveys some of the major nonparapsychological issues that have fascinated researchers into mediumship. These include the nature and prevalence of the mediumistic trance, the varieties of mediumistic mentation, the evolution of mediumship over time, the dramatic capabilities of the subconscious, and the relationship between mediumship and psychopathology. The third paper focuses on positive aspects of mediumship, and in particular its connection with various forms of artistic and practical creativity, as well as its potential for personal development or transformation. The fourth paper considers whether mediumship ever indicates that human personality survives bodily death, or whether even the best cases instead indicate psychic functioning among the living. The author surveys types of mediumship that have been especially relevant to this question, and advocates the revival of so-called proxy sittings with mediums. The final paper recounts a period in France's recent history during which a group of researchers lobbied to have parapsychology broadened into a multidisciplinary field embracing (in additional to strictly experimental and proof-oriented investigations) wide-ranging enquiries that could be applied to mediumship and other apparent instances of psychic functioning in real-life settings. This issue of the JSE is then filled out, as usual, with correspondence and substantive book reviews.